734 ACUTE CARE PATHWAYS FOR OLDER MAJOR TRAUMA PATIENTS: A SURVEY OF UK PRACTICE. (8th March 2022) - Jarman, H; Cole, E; Crouch, R; Halter, M; Peck, G
Abstract: Introduction: Major trauma is a significant health burden for older patients, with worse clinical outcomes when compared to younger people. Various clinical models exist however it is not clear which have most benefit for older patients. This study aimed to map the current provision of clinical pathways and services for older people with major trauma in the United Kingdom (UK). Methods: A cross-sectional online survey was undertaken. Case vignettes designed to reflect 'typical' older major trauma patients were embedded within the survey. The survey was distributed via trauma network managers and social media, inviting responses from all UK hospitals receiving trauma patients in 2020. Fixed choice questions were analysed with descriptive statistics and free text responses categorised into themes. The survey was not deemed to be research using the UK Health Regulatory Authority tool. Results: Responses were received from 20/27 Major Trauma Centres (MTCs), 33 Trauma Units (TUs) and two local emergency hospitals. Older patients were defined by age (range 55 to 82 years) or frailty status. Frailty assessment was routinely performed in more than two-thirds (69.1%) of locations. Availability of trauma-specific guidance for older patients varied, and was greater in TUs than MTCs. Analysis of the vignettes showed wide variability in the admission and subsequent interventions for older major trauma patients across hospitals. Qualitative data showed pre-injury health status, staff availability, and day of the week were factors leading to variation within individual hospitals. Conclusion: There is wide variation in the processes of care and pathways for older major trauma patients in the UK. Whilst lack of standardisation may be a result of local service configuration this has the potential to impact negatively on quality of care, multi-disciplinary working and outcomes. Understanding the range of variation in practice provides opportunity to identify good practice and areas for improvement.